2022
DOI: 10.21037/atm-22-3236
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of fecal microbiota transplantation for the induction of remission in active ulcerative colitis: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background: Fecal microbiota transplantation (FMT) is a novel management strategy for ulcerative colitis (UC). However, its effectiveness remains controversial. This study sought to assess the effectiveness of FMT in the treatment of active UC by performing a meta-analysis of randomized controlled trials (RCTs).Methods: We searched the Cochrane, Embase, PubMed, and Web of Science databases from their inception to December 2021. RCTs that recruited patients with active UC and treated them with FMT, a placebo or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Importantly, AEs and SAEs were reported in only two of their four studies, and none of their SAEs were attributable to death. In another meta-analysis of FMT safety in a UC population of all ages from 2022, SAEs occurred at a pooled rate of 10% [ 45 ]. Unfortunately, it is unclear if there was any mortality in this data set.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, AEs and SAEs were reported in only two of their four studies, and none of their SAEs were attributable to death. In another meta-analysis of FMT safety in a UC population of all ages from 2022, SAEs occurred at a pooled rate of 10% [ 45 ]. Unfortunately, it is unclear if there was any mortality in this data set.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the studies had very few participants and were not conducted using reliable methods. [9,10,39] In addition to the inherent limitations of reticulated meta-trials, our analysis also has limitations. Thorough comparative analyses of all drugs were limited to trials of induction therapy, making it difficult to assess their effectiveness due to differences in the design of maintenance therapy trials.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have shown that microbiome therapies, including probiotics, synbiotics, and fecal microbiota transplant (FMT), are also a potential Medicine therapy for inflammatory bowel disease and irritable bowel syndrome. [9,10] The majority of research has directly contrasted the effectiveness of placebos and biological agents with that of small molecule medications. [11][12][13] The effects of various biologics or between biologics and small molecule medications have only been directly compared in a limited number of trials.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using higher doses of donor feces ( > 275 g) were associated with higher response rates (52% vs. 30%) than those using lower doses. Similarly, subgroup analysis by Wei et al [ 83 ] found benefit of FMT in induction of remission of UC only when the cumulative dose was higher than 300 g (risk ratio [RR], 1.85; 95% confidence interval [CI], 1.22–2.83) but not in lower doses. To achieve these doses, several sessions may be required, and there may be differences in optimum doses for induction versus maintenance of remission in IBD.…”
Section: Procedure-related Factors and Outcome Determinants In Fmtmentioning
confidence: 96%